Les clauses restrictives d’un contrat d’agent - Amyot, Bernard (Assurances)

(untitled) (HEC Montréal, 1996)
Insurance companies often impose contractual limits in agency contracts on the right to non-competition following the expiry of a contract. These include non-competition, non-solicitation and penalty clauses. In his article, the author examines the rules of proof and validity applicable to such restrictive clauses in an employment contract as well as the recourse available to a company if restrictive clauses are found reasonable.